Continuous NAPL loss rates using subsurface temperatures - Stockwell, Emily Beth, author; Sale, Tom, advisor; Blotevogel, Jens, committee member; Ham, Jay, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: natural source zone depletion; remediation; biodegradation; thermal; petroleum